GROUP B STREPTOCOCCUS NEONATAL MENINGITIS—LESS COMMON CAUSE OF NEONATAL MENINGITIS IN PAKISTAN AND DISPARITY BETWEEN CSF CULTURE AND OTHER PARAMETERS: Group B Streptococcus Neonatal Meningitis - Hussain, Shabbir; Ahmad, Tariq Mahmood; Tarar, Saba Haider (Pakistan Armed Forces Medical Journal, 2015)
Neonatal bacterial meningitis is a devastating illness with significant mortality and morbidity. Incidence and etiology of neonatal bacterial sepsis and meningitis varies among developed and developing countries. We are reporting a case of 6 days old neonate who presented with fever, refusal to take feed and then followed by an episode of seizure activity. Laboratory parameters for complete sepsis screening including cerebrospinal fluid (CSF) and metabolic screening were absolutely normal for his age, but CSF culture revealed growth of group B Streptococcus (Streptococcus agalactiae). Patient was treated successfully without any morbid sequel.